Birytualny (?) pochówek z cmentarzyska kultury wielbarskiej w Weklicach, gm. Elbląg, stanowisko 7 - Natuniewicz-Sekuła, Magdalena (Museum of Archaeology-History in Elblag, 2007)
P. 151-158 : ill. ; 30 cm
Bibliography p. 157-158
Summary in English
Keywords: Roman period -- Poland; Wielbark culture; Wielbark culture cemeteries; Wielbark culture funeral rite; Wielbark culture grave goods; human skeletal remains; anthropological analysis; Weklice, Elbląg commune (Poland)

Unikatowy, "brązowy" dzban rzymski w stylu egiptyzującym z Weklic : nowe odkrycia... - Natuniewicz-Sekuła, Magdalena (Instytut Archeologii Uniwersytetu Łódzkiego, 2010)
Bibliogr. s. 415-416
S. 397-416 : il.
Keywords: Roman period -- Poland; Wielbark culture cemeteries; Wielbark culture grave goods; Roman metal jugs; Roman metal jugs -- provenance; technological and stylistic analysis of metal objects; Weklice, Elbląg commune (Poland)

Wczesnorzymskie szkieletowe pochówki o orientacji zachodniej z cmentarzyska w Weklicach, stan. 7, pow. Elbląg : przyczynek do analizy zwyczajów pogrzebowych ludności kultury wielbarskiej - Natuniewicz-Sekuła, Magdalena (Muzeum Archeologiczne, 2007)
Bibliography p. 493-495
P. 475-496 : ill.
German summary
Keywords: early Roman period -- Poland; Wielbark culture; Wielbark culture funeral rite; Wielbark culture skeletal cemeteries; Wielbark culture graves; orientation of burials; Wielbark culture grave goods; human skeletal remains; anthropological analysis; review of archaeological finds; Weklice, Elbląg commune (Poland)

"Neue" Funde vom Gräberfeld Wielbark (Willenberg) : ein Beitrg zur weiteren Suche nach verlorenen Materialien - Natuniewicz-Sekuła, Magdalena (Institute of Archaeology University of Warsaw, 2003)
P. 81-86 : ill. ; 25 cm
Bibliography p. 85-86
Keywords: Roman period -- Poland; archaeological collections -- Poland; Wielbark culture cemeteries; review of archaeological finds; archaeological archive records; Wielbark (Poland)

Cmentarzysko germańskich elit w centrum bursztynowego wybrzeża : Weklice, gm. Elbląg - Natuniewicz-Sekuła, Magdalena (Published by Edytor, 2011)
P. 123-130 : ill. ; 24 cm
Bibliography p. 25
English summary
Keywords: Goths (people); Amber Road; Wielbark culture; Wielbark culture cemeteries; Wielbark culture funeral rite; Wielbark culture grave goods; Amber Road and cultural contacts; Weklice, Elbląg commune (Poland)

Osady z okresu rzymskiego w Kołozębiu i Poświętnem : studium krytyczne wyników wykopalisk - Natuniewicz-Sekuła, Magdalena (Institute of Archaeology University of Warsaw, 2006)
P. 115-144 : ill. ; 30 cm
Bibliogaphy p. 123-124
Keywords: Roman period -- Poland; Roman period settlement -- Poland; results of archaeological research; Roman period pottery; Roman period pottery -- typology; Roman period pottery -- ornamentation; Kołoząb, Płońsk county (Poland); Poświętne, Płońsk county (Poland)

Nowe znaleziska ze starych wykopalisk : zabytki z okresu wpływów rzymskich w zbiorach Muzeum w Elblągu - Natuniewicz-Sekuła, Magdalena (Stowarzyszenie Naukowe Archeologów Polskich, 1999)
P. 115-131 : ill. ; 30 cm
Bibliography p. 122-124
Keywords: Muzeum w Elblągu [Museum in Elbląg] (Elbląg, Poland); archaeological collections -- Poland; Roman period -- Poland; review of archaeological finds

"Nowe" znaleziska ze starych wykopalisk : ocalałe materiały archeologiczne z okresu wpływów rzymskich ze stanowisk z okolic Elbląga - Natuniewicz-Sekuła, Magdalena (Instytut Archeologii Uniwersytetu Warszawskiego, 2000)
s. 105-161
German summary
Keywords: Roman period -- Poland; archaeological collections -- Poland; archaeological collections -- typology of objects; results of archaeological research -- verification; catalogue of archaeological finds; research demands; Elbląg, voiv. mazursko-warmińskie-region (Poland)

Grób 7 z cmentarzyska w Szpondowie, stanowisko II, powiat płoński - Natuniewicz-Sekuła, Magdalena (Institute of Archaeology University of Warsaw, 2001)
P. 135-139 : ill. ; 30 cm
Summary in German
Keywords: La Tene-Roman period -- Poland; Przeworsk culture; Przeworsk culture cemeteries; Przeworsk culture grave goods; Przeworsk culture funeral rite; late La Tene fibulae; chronology of site; Szpondowo, Płońsk county (Poland)

Sprawozdanie z badań wykopaliskowych na cmentarzysku kurhanowym w Odrach, pow. Chojnice, w latach 1962-1963 - Chyżewska, Maria (Zakład Narodowy im. Ossolińskich, 1966)
P. 107-125, [1] k. złoż. : oll. ; 25 cm
English summary
Bibliographical footnotes
Keywords: Roman period -- Poland; Roman period barrow cemeteries; Wielbark culture; Wielbark culture cemeteries; Wielbark culture barrows; Wielbark culture pottery; Odry (Poland)

Chronologia ceramiki kultury wielbarskiej w świetle dotychczasowego stanu badań - Wołągiewicz, Ryszard (1933–1994) (Zakład Narodowy im. Ossolińskich, 1987)
Anexes: 1, Zespoły zwarte z typami naczyń występujących ze sobą oraz z wyznacznikami chronologii. - 2,Datowanie ceramiki kultury wielbarskiej. - 3, Wyznaczniki chronologiczne towarzyszące ceramice
P. 169-208, [1] folded leaf : ill., tables ; 25 cm
Bibliography p. 203-205
German summary
Keywords: pre-Roman-Roman period -- northern Poland; Wielbark culture; Wielbark culture pottery; Wielbark culture cemeteries; Wielbark culture grave goods; Wielbark culture pottery -- typology

Wykaz publikacji naukowych prof. dr. hab. Wojciecha Szymańskiego - Natuniewicz-Sekuła, Magdalena (Uniwersytet Marii Curie-Skłodowskiej, 2003)
p. 17-28
Keywords: Szymański, Wojciech (1932-; historian; archaeologist); personal bibliographies

The Craft of the Goldsmith in Wielbark Culture in the Light of the Finds from the Cemetery at Weklice, Elbląg Commune and Other Necropolis of Roman Period from Elbląg Heights. Technological Studies of Selected Aspects - Natuniewicz-Sekuła, Magdalena (Instytut Archeolgoii i Etnologii Polskiej Akademii Nauk, 2017)
The paper presents selected aspects the goldsmithery of Wielbark culture in Roman period. Based on analyzes of chemical composition of fi nds from the cemetery at Weklice, site 7, Elbląg commune and fi nds from selected cemeteries of Roman period located on the Elbląg Heights, three main groups of raw materials were separated: gold, silver and copper alloys. They were also discussed selected techniques of production of jewelry and costume elements, most commonly used by Wielbark culture goldsmiths: casting, forging, fi ligree, granulation, gilding, soldering. Based on the collected data it was found that the Wielbark culture goldsmith workshop was one of the highest technology levels of ancient goldsmithery.
ill. ; 25 cm
Keywords: Wielbark culture; Roman period; goldsmithery; gold; silver and copper alloys; chemical composition analyzes

"Jeździec bez głowy" et alli, czyli znaleziska ostróg z cmentarzyska kultury wielbarskiej w Weklicach - Kontny, Bartosz (1971– ) (Instytut Archeologii Uniwersytetu Łódzkiego, 2010)
Bibliogr. s. 342-345
Bibliography p. 342-345
P. 333-345 : ill.
Keywords: Roman period -- Poland; Wielbark culture; Wielbark culture cemeteries; Wielbark culture grave goods; Wielbark culture spurs; Weklice, Elbląg commune (Poland)

Selected children’s burials from the Wielbark culture cemetery at Weklice, Site 7, Elbląg commune, warmińsko-mazurskie voivodeship - Natuniewicz-Sekuła, Magdalena; Skóra, Kalina (Institute of Archaeology and Ethnology Polish Academy of Sciences, 2016)
The paper discusses children’s burials from the Wielbark culture cemetery at Weklice, Site 7, excavated in 1984–2013. The results of the anthropological analysis and observations on the characteristics of the burial rites for infans I and II are presented against the background of other finds from the Wielbark culture territory. The issue of the lack of children’s burials at the cemeteries of the Wielbark culture is dealt with; furthermore, opportunities of identification of such burials with archaeological methods are discussed. The child’s position in the social structure of the discussed cultural unit is analysed
ill. ; 24 cm
Keywords: Wielbark culture; children's burials; archaeology of childhood; anthropology; demography; social position

Nietypowe zabiegi pogrzebowe w kulturze wielbarskiej na przykładzie grobu 471 z cmentarzyska w Weklicach, stanowisko 7, gm. Elbląg - Kontny, Bartosz (1971– ) (Institute of Archaeology University of Warsaw. Department of Archaeology of Ancient Europe, 2004)
P. 305-312 : ill.; 30 cm
Bibliography p. 310
Keywords: Roman period -- Poland; Wielbark culture; Wielbark culture cemeteries; Wielbark culture funeral rite; human skeletal remains; anthropological analysis; Weklice, Elbląg commune (Poland)

Archeologia Polski T. 32 (1987) Z. 1, Kronika - Andrzejowski, Jacek (Zakład Narodowy im. Ossolińskich, 1987)
Seminarium "Ceramika kultury wielbarskiej: problemy typologii i chronologii w świetle analizy zespołów zwartych". Malbork-Gdańsk 25-26 listopada 1985 r.
P. 239-241 ; 25 cm
Bibliographical footnotes
Keywords: Iron Age -- Poland; conference (Malbork-Gdańsk, Poland; 1985); Wielbark culture; Wielbark culture pottery; Wielbark culture pottery -- typology

Archeologia Polski T. 27 (1982. - 1983) Z. 2, Recenzje - Niewęgłowski, Andrzej. Reviewer (Zakład Narodowy im. Ossolińskich, 1982)
Û. V. Kuharenko, Mogilnik Brest-Trišin, Wyd. "Nauka", Moskva 1980, ss. 127
P. 480-486 ; 25 cm
Bibliographical footnotes
Keywords: Iron Age -- Belarus; Wielbark culture; Wielbark culture cemeteries; Wielbark culture grave goods; Wielbark culture pottery; Wielbark culture fibulae; Wielbark culture fibulae -- typology; Wielbark culture jewellery; chronology of cemetery; Brześć-region (Belarus)

Nowy kurhan z okresu rzymskiego w Łukawicy, pow. Lubaczów - Talar, Antoni (Zakład Narodowy im. Ossolińskich, 1970)
P. 399-403 : ill. ; 25 cm
Bibliographical footnotes
English summary
Keywords: Roman period -- Poland; Wielbark culture; Wielbark culture barrows; Łukawica (Poland)

Unikatowy dzban brązowy z Kowalewka, woj. poznańskie - Skorupka, Tomasz (Instytut Archeologii i Etnologii Polskiej Akademii Nauk, 1997)
ill. ; 29 cm
Keywords: Roman period -- Poland; Wielbark culture; Wielbark culture cemeteries; Wielbark culture grave goods; Roman period bronze jugs; Kowalewko (Poland)

Sprawozdania Archeologiczne T. 22 (1970), Omówienia i recenzje - Godłowski, Kazimierz (Zakład Narodowy im. Ossolińskich, 1970)
Odry, cmentarzysko kurhanowe z okresu rzymskiego w pow. chojnickim, praca zbiorowa pod redakcją Jerzego Kmiecińskiego, Acta Archaeologica Lodziensia, nr 15, Łódź 1968, ss. 137, 68 tabl. 13 ryc. 10 tab.
P. 493-499 ; 25 cm
Keywords: Roman period -- Poland; Roman period barrow cemeteries; Wielbark culture; Wielbark culture cemeteries; Wielbark culture funeral customs and rites; Odry (Poland)

Wielbark Kultur im Dobriner Land 30 Jahre später. Aktueller Stand der Forschung und weitere Forschungsperspektiven - Kurpiewski, Artur; Lewandowska, Jadwiga (Instytut Archeolgoii i Etnologii Polskiej Akademii Nauk, 2016)
The state of research on the Wielbark culure in the area of the Dobrzyń Land leaves much to be desired. Exactly thirty years ago Krystyna Hahuła wrote her MA thesis titled Early Pre-Roman and Roman period in the Interfluve of Vistula, Drwęca and Skrwa rivers. A few years later the author’s main findings were published in a small text called Wielbark Culture on the Dobrzyń Land. For almost three decades this work has served as a source of knowledge about settlements in the Roman period for this area. Research conducted since the beginning of the twenty-first century has shed some new light on the transformation of settlements of the region. This text does not claim to be comprehensive on the subject; it is merely an attempt to signal changes taking place in the Roman period in the Vistula, Drwęca and Skrwa interfluve in the context of the latest findings
ill. ; 25 cm
Keywords: Dobrzyń Land (Poland); Roman period; Wielbark culture

Cmentarzysko ludności kultury wielbarskiej w Rzyszczewie, woj. Koszalin - Machajewski, Henryk (Zakład Narodowy im. Ossolińskich, 1983)
P. 123-139 : ill. ; 25 cm
English summary
Bibliographical footnotes
Keywords: Roman period -- Poland; Wielbark culture; Wielbark culture cemeteries; Wielbark culture grave goods; Rzyszczewo (Poland)

Sprawozdanie z badań w latach 1964-1965 na cmentarzysku z okresu rzymskiego w Odrach, pow. Chojnice - Posmykiewicz, Maria (Zakład Narodowy im. Ossolińskich, 1969)
P. 111-117 : ill. ; 25 cm
English summary
Bibliographical footnotes
Keywords: Roman period -- Poland; Wielbark culture; Wielbark culture cemeteries; Wielbark culture grave goods; Odry (Poland)

A Wielbark Culture piece of weaponry? : remarks concerning the astonishing gind at the cemetery at Crosno (Krossen) - Kontny, Bartosz (1971– ) (Klaipeda University Press, 2007)
Bibliography p. 167-169
P. 160-170 : ill.
Lithuanian summary
Keywords: Roman period -- Poland; Wielbark culture; Wielbark culture cemeteries; Wielbark culture grave goods; weapon finds in Wielbark culture graves; Roman period swords; Roman period sword hilts; Krosno, Pasłęk commune (Poland)